Influence of commercial starter culture on fermentation dynamics and quality characteristics of yogurts obtained with different formulations - Vénica, Claudia Inés (2022)
BACKGROUND: Four commercial starter cultures containing Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus (S1, S2, S3 and S4; S3 also contained Limosilactobacillus fermentum) were compared for fermentation, volatile flavor compounds, physicochemical parameters and microbiology, in yogurt prepared from three milk base formulations with increased protein (B1, B2 and B3). RESULTS: The fermentation patterns differed among starters, with Yoflex Mild 1.0 (S4) and SLB95 (S2) showing the longest fermentation time, depending on the formulation. At 21 days, S. thermophilus counts were similar among starters and higher than 8.52 log CFU mL−1, for all yogurts. The highest counts (6.86 log CFU mL−1) for L. delbrueckii subsp. bulgaricus was found for S2 yogurts made from whey protein hydrolysate (B3). Minor water-holding capacity was detected for YF-L811 (S1) yogurts. Yoflex Harmony 1.0 (S3) starter containing Lim. fermentum produced a distinctive volatile profile characterized by aldehydes with respect to yogurts prepared with S1, S2 and S4, which were characterized by ketones. CONCLUSION: Results indicate the usefulness of carrying out studies similar to the present one to select the most appropriate process conditions depending on the desired product.